RUMAH GADANG: CONTEXTUAL MATHEMATICS IN A SOCIO-CULTURAL CONTEXT FOR NUMERACY ASSESSMENT - Usman, Zea Zisman; Rahman, Hadi Nur (Ethnomath Association in cooperation with Universitas Negeri Yogyakarta, 2024)
Numeracy is an important competency that is measured by Asesmen Kompetensi Minimum (AKM/Minimum Competency Assessment). To improve student numeracy, innovation is needed in learning mathematics, one of which is by using Ethnomathematics. The cultural object that becomes the benchmark is Rumah Gadang. Before producing effective and efficient models, devices, and learning methods based on the ethnomathematics of Rumah Gadang oriented to student numeracy, it is necessary to conduct a study first, so this research aims to conduct a literature review related to numeracy in the Rumah Gadang. The data collection method is a literature study, where the data is analyzed through three stages, namely Data Reduction, Data Presentation and Verification. Based on this research, it was found that the results of the researchers' contextual exploration of Rumah Gadang can be associated with 4 domains of mathematics material, namely numbers, geometry and measurement, algebra and data and uncertainty. Therefore, Rumah Gadang can be used as a learning material that is quite varied in terms of contextual in ethnomathematics-based mathematics learning, especially in terms of writing socio-cultural context questions in a numeracy assessment.